La voie d’Aquitaine entre Tolosa (Toulouse, Haute-Garonne) et Carcaso (Carcassonne, Aude) : stations et sites de bord de route - Michel Passelac (Gallia)
Ground and aerial surveys have yielded significant data on roadside stations along the Via Aquitania, between Toulouse and Carcassonne. The article reports on the sites referred to in the antique Itineraries – state stations – established primarily in urban areas. The location of a mutatio, Ad Vigesimum, is specified. Adjacent to these stations, a greater number of roadside sites has been identified: private institutions intended primarily for travellers and transporters. With a surface area of 0.5-2.0 hectares, they line the road on one or both sides and are located near a stream or spring. There are no sure signs of multiple activities, but they often contain remains of blacksmiths’ forges, food preparation areas, and stables. The significant presence of these “service stations” throughout the Roman period reflects the importance of this route, which did not follow the path of any known waterways, as well as its crucial role in land use and in the economy of the region.